Unraveling the Language and Ideology: A Critical Discourse Analysis of Permendikbudristek No.30 Year 2021 in Republika Newspaper - Rosdiana, Rina; Budiana, Sandi; Mahajani, Tri (ppjbsip, 2023)
This study examines the ideological construction in the national newspaper Republika (a newspaper with an ideological perspective on Islam in Indonesia and reader responses to the news regarding Permenristekdikti No. 30 of 2021. The method used in this study is critical discourse analysis. The research technique is qualitative descriptive. This research has explained the ideological construction through the Fairclough framework for critical discourse analysis (CDA) by applying it to news texts, articles/opinions from experts, editorials/editorials, and main reports published mid to late November 2019, a total of 13 articles, in details, five articles in the form of news, four articles including the main report, 1 article in the form of articles/ opinions from education experts, and 2 in the form of editorials, only 1 article was published by Republika which is a form of support for this regulation. An in-depth analysis was carried out on intertextuality. In the modality analysis, the use of modalities in the news text studied was dominated by epistemic modalities compared to three other modalities, namely intentional, deontic, and dynamic modalities. The use of these modalities in positive or negative sentences represents a certain ideology (Requests from education experts and Islamic mass organizations that Permendikbudristek Number 30 of 2021 be reviewed; accommodate religious guidance, Islamic teachings, Pancasila, the 1945 Constitution, and cultural values in Indonesia. An ideology can be detected by analyzing the linguistic corpus data on the selected diction in the concordance series. The corpus data in the concordance series strengthens the ideology of the newspaper. Among the word series in concordance are Permendikbudristek (80), violence (72), agreement (44 ), criticism (10), and revised (5).This study examines the ideological construction in the national newspaper Republika (a newspaper with an ideological perspective on Islam in Indonesia and reader responses to the news regarding Permenristekdikti No. 30 of 2021. The method used in this study is critical discourse analysis. The research technique is qualitative descriptive.This research has explained the ideological construction through the Fairclough framework for critical discourse analysis (CDA) by applying it to news texts, articles/opinions from experts, editorials/editorials, and main reports published mid to late November 2019, a total of 13 articles, in details, five articles in the form of news, four articles including the main report, 1 article in the form of articles/ opinions from education experts, and 2 in the form of editorials, only 1 article was published by Republika which is a form of support for this regulation. An in-depth analysis was carried out on intertextuality. In the modality analysis, the use of modalities in the news text studied was dominated by epistemic modalities compared to three other modalities, namely intentional, deontic, and dynamic modalities. The use of these modalities in positive or negative sentences represents a certain ideology (Requests from education experts and Islamic mass organizations that Permendikbudristek Number 30 of 2021 be reviewed; accommodate religious guidance, Islamic teachings, Pancasila, the 1945 Constitution, and cultural values in Indonesia. An ideology can be detected by analyzing the linguistic corpus data on the selected diction in the concordance series. The corpus data in the concordance series strengthens the ideology of the newspaper. Among the word series in concordance are Permendikbudristek (80), violence (72), agreement (44 ), criticism (10), and revised (5).